2009
DOI: 10.1557/jmr.2009.0116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of specimen preparation, microstructure anisotropy, and residual stresses on stress–strain curves of rolled Al2024 T351 as derived from spherical indentation tests

Abstract: In the present work, a previously developed neural network approach for analyzing spherical indentation experiments is applied to prestressed specimens to determine the effect of residual stresses on the identified stress–strain curves. Within this scope, a comparison to other measurement errors has been made, which are caused by surface preparation and anisotropy of the material. To validate the experimental and analysis approach, the effect of compressive and tensile prestresses was also simulated using a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Because of the large strains that occurred during this test, it was more sensitive to the yield stress behaviour around a 10% plastic strain. It showed larger uncertainties below, above and, in particular, near the yield point [13][14][15]. Thus, this approach is favourable for studies that investigate the deformation behaviour of specimens under significant plastic deformation.…”
Section: Indentation Testmentioning
confidence: 95%
“…Because of the large strains that occurred during this test, it was more sensitive to the yield stress behaviour around a 10% plastic strain. It showed larger uncertainties below, above and, in particular, near the yield point [13][14][15]. Thus, this approach is favourable for studies that investigate the deformation behaviour of specimens under significant plastic deformation.…”
Section: Indentation Testmentioning
confidence: 95%
“…The prediction of rising or falling material hardness, based on residual stresses and contact pressure of spherical indentation tests was investigated by several groups via experimental and FEM simulations. Heerens et al (2009) presented a model that allows to compute the change in hardness for arbitrary in-plane biaxial residual stress states including the special cases of uniaxial, equibiaxial, and pure shear residual stress. Relevant for this review is the way this model was found.…”
Section: Predictivementioning
confidence: 99%
“…Therefore, as major outcome of the applied machine learning approach, it can be concluded that both the normalized von-Mises stress and hydrostatic pressure are equally important to solve the problem. The model published by Heerens et al (2009) is based on this insight and would not exist without the intermediate step of using the ANN. While the ANN was descriptive and limited to the range of training data, the derived model is general and predictive.…”
Section: Predictivementioning
confidence: 99%
“…A three-dimensional finite element model was used, which has been validated regarding its accuracy and pre-stress application elsewhere [19]. The finite element model is presented in Fig.…”
Section: Theoretical Model 21 Finite Element Simulationsmentioning
confidence: 99%